2011
DOI: 10.1002/ange.201105415
|View full text |Cite
|
Sign up to set email alerts
|

Durch N‐heterocyclische Carbene katalysierte Dominoreaktionen

Abstract: Während sich die organokatalytischen Dominoreaktionen (auch Organokaskadenkatalysen genannt) im letzten Jahrzehnt zu einem wichtigen Hilfsmittel in der Synthesechemie entwickelt haben, fand die Anwendung von N‐heterocyclischen Carbenen (NHCs) als Katalysatoren in Dominoreaktionen erst in den letzten drei Jahren zunehmend Beachtung. Unter Berücksichtigung der besonderen Aktivierungsmodi der Substrate durch die NHC‐Katalysatoren ist eine Unterscheidung zwischen einer einzelnen chemischen Transformation und einer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
33
0
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 331 publications
(40 citation statements)
references
References 135 publications
0
33
0
7
Order By: Relevance
“…action led to the formation of enantioenriched 3,3'-thiopyrrolidonyl spirooxindoles 411 in excellent yields, dr and ee values.T he catalytic model mentioned earlier [133,136] could possibly also be operative in this case,a st he protection of the 9-OHg roup of the catalyst with an OBn group resulted in ac omplete loss of the enantioselectivity in this reaction. [162] Xu, Wang, and co-workers developed an asymmetric domino allylic alkylation/cyclization reactionb etween 3-hydroxyoxindoles 412 and Morita-BaylisHillmanc arbonates 413 to affords pirooxindoles 414 bearing the a-methylene-g-butyrolactone motif (Scheme 106).…”
Section: Scheme103 Synthesis Of 3-amino-substituted Isoindolinonesmentioning
confidence: 98%
“…action led to the formation of enantioenriched 3,3'-thiopyrrolidonyl spirooxindoles 411 in excellent yields, dr and ee values.T he catalytic model mentioned earlier [133,136] could possibly also be operative in this case,a st he protection of the 9-OHg roup of the catalyst with an OBn group resulted in ac omplete loss of the enantioselectivity in this reaction. [162] Xu, Wang, and co-workers developed an asymmetric domino allylic alkylation/cyclization reactionb etween 3-hydroxyoxindoles 412 and Morita-BaylisHillmanc arbonates 413 to affords pirooxindoles 414 bearing the a-methylene-g-butyrolactone motif (Scheme 106).…”
Section: Scheme103 Synthesis Of 3-amino-substituted Isoindolinonesmentioning
confidence: 98%
“…The diene moiety is virtually planar, with a torsion angle C2-C6-C21-C22 of 177.4(3)8. The lengths of the two C=C bonds are 1.362(4) (C2=C6) and 1.356(3) (C21=C22), whereas the length of the connecting C-C single bond (C6-C21) amounts to 1.424 (3) . As in the case of the 2,2-diamino enols 3 a, 3 c, and 3 e, the crystal packing of the diamino dienol 3 g did not indicate the involvement of the hydroxy group in hydrogen bonding (see the Supporting Information).…”
mentioning
confidence: 99%
“…[3][4][5] In Seebachs terminology, the aldehyde undergoes a 1 -d 1 umpolung. [6] Postulated in 1958, [1,2] the first successful generation of diamino enols from aldehydes and carbenes, and their characterization by in situ NMR spectroscopy was reported by us in 2012.…”
mentioning
confidence: 99%
“…[3] In the last decade, the N-heterocyclic carbene (NHC) catalyzed annulation reactions emerged as powerful methods for various heterocycles. [7] In 2004, Bode et al and Glorius et al independently reported the pioneering NHC-catalyzed [3+2] annulation of enals with aldehydes to give g-butyrolactones (Scheme 1 a). [8] Then, g-lactams were synthesized by reaction with imines.…”
mentioning
confidence: 97%